ANALISIS PENGARUH PERSAINGAN USAHA PASAR TRADISIONAL TERHADAP PASAR MODERN PERATURAN DAERAH KOTA MEDAN - Fajriawati, Fajriawati (Varia Justicia, 2017)
The Effect of Traditional Market Competition on Modern Market in Local Regulation No. 53 / M-DAG / PER / 12/2008 concerning the arrangement and development of traditional markets and Shopping Centers and Modern Stores. And in article 2 of Law Number 5 Year 1999 we can see how the arrangement and layout of service, layout, business license for the common good. From the results of this study using the Normative Research and Empirical Research. The closer to legislation that focuses on the rule of law as its central to know the Influence Analysis of Competition of traditional market in this case policy related to license of establishment of modern market is not comprehensive because related to partnership as mandated in Perpres and permendagri not regulated further. Regulations on partnerships can maintain traditional markets that are fundamental to eliminating the disparity between modern markets.